1994
DOI: 10.1002/mpo.2950230209
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological evaluation of children with intracranial tumors: Impact of treatment modalities

Abstract: Antineoplastic treatment has a deleterious effect on intellectual functions, which is mainly attributable to radiotherapy. With the object of determining the neuropsychological disturbances associated with brain irradiation in the child, and to try to differentiate them from the effects caused by the other types of treatment (surgical and chemotherapy) as well as from the effects of the tumor itself, a cross-sectional study was carried out in 25 survivors of medial edge intracranial tumors. In order to monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
3
8
0
1
Order By: Relevance
“…2). The present study supports a few of the earlier investigations that claim cognitive dysfunction in the form of learning difficulties and impairment of memory (Spencer 1998;Garcia et al 1994;Kingma et al 1993) after methotrexate treatment. Williams et al (1992), in their experiment on monozygotic twins, observed neuropsychological dysfunction in both methotrexate-treated (for leukemia) and untreated (normal children) subjects.…”
Section: Discussionsupporting
confidence: 92%
“…2). The present study supports a few of the earlier investigations that claim cognitive dysfunction in the form of learning difficulties and impairment of memory (Spencer 1998;Garcia et al 1994;Kingma et al 1993) after methotrexate treatment. Williams et al (1992), in their experiment on monozygotic twins, observed neuropsychological dysfunction in both methotrexate-treated (for leukemia) and untreated (normal children) subjects.…”
Section: Discussionsupporting
confidence: 92%
“…in childhood leukaemia [33], 25 studies are cited that report negative effects of irradiation on cognitive meaAlthough the underlying mechanisms of irradiationinduced neurocognitive dysfunction are not yet fully unsurements. Other studies indicate that children who receive CRT develop impaired visual and verbal memory, derstood, present evidence indicates that CRT may induce neurocognitive dysfunction, younger children being the attention capacity, verbal fluency, and visual discrimination skills, verbal IQ, and reading and spelling [34,35]. most susceptible to these injuries.…”
Section: Effects Of Treatment For Pituitary Tumoursmentioning
confidence: 63%
“…Consequently, they do not represent a real control group for children treated with chemotherapy only. Nevertheless, several studies on children surviving medial edge intracranial tumours who underwent brain irradiation showed a deterioration in a number of specific cognitive functions (Kun and Mulhern, 1983;Packer et al, 1983;Bendersky et al, 1988;Duffner et al, 1988;Morrow et al, 1989;Garcia-Perez et al, 1994): the most affected items were memory followed by attention, sequential processing and visual-spatial organisational skills. In the study of Fouladi, preschool children (i.e.…”
Section: Discussionmentioning
confidence: 99%